Analysis of the association of polymorphism in the osteoprotegerin gene with susceptibility to chronic kidney disease and periodontitis - Baioni, C. S.; de Souza, C. M.; Braosl, A. P. Ribeiro; Luczyszyn, S. M.; da Silva, M. A. Dias [UNESP]; Ignacio, S. A.; Machado, M. A. Naval; Martins, W. D. Benato; Riella, M. C.; Pecoits-Filho, R.; Trevilatto, P. C. (Wiley-Blackwell, 2008)
Background and Objective: Chronic kidney disease (CKD) is a complex disorder, which results in several complications involving disturbance of mineral metabolism. Periodontal disease is an infectious disease that appears to be an important cause of systemic inflammation in CKD patients. Periodontal disease is characterized by clinical attachment loss (CAL) caused by alveolar bone resorption around teeth, which may lead to tooth loss. Osteoprotegerin (OPG) is a key regulator of osteoclastogenesis. Polymorphisms are the main source of genetic variation, and single nucleotide polymorphisms (SNPs) have been reported as major modulators of disease susceptibility. The aim of this study was to investigate the association of a polymorphism located at position -223 in the untranslated region of the OPG gene, previously known as -950, with susceptibility to CKD and periodontal disease.Material and Methods: A sample of 224 subjects without and with CKD (in hemodialysis) was divided into groups with and without periodontal disease. The OPG polymorphism was analyzed by polymerase chain reaction and restriction fragment length polymorphism.Results: No association was found between the studied OPG polymorphism and susceptibility to CKD or periodontal disease.Conclusion: It was concluded that polymorphism OPG-223 (C/T) was not associated with CKD and periodontal disease in a Brazilian population. Studies on other polymorphisms in this and other genes of the host response could help to clarify the involvement of bone metabolism mediators in the susceptibility to CKD and periodontal disease.
Keywords: chronic kidney disease; periodontal disease; osteoprotegerin; genetic polymorphism